Heat treatment responses in oil palm (Elaeis guineensis) genotypes and their impact on germination and seedling growth - OSEI, SAMUEL ADU; DARKWAH, DICKSON OSEI; SAPEY, ENOCH; BANAFO, SAMUEL ADDO; OSSOM, JOHNNY SACKITEY; DUAH-BOATENG, ISAAC; NYANFUL, LEWIS; FRANCIS, OSEI; GYAMERAH, EDWARD OWUSU; GODSON, ARTHUR; MICHAEL, TENADU; KUSAN, JOCHEBED; et al. (Asian Journal of Agriculture, 2026)
Abstract. Osei SA, Darkwah DO, Sapey E, Banafo SA, Ossom JS, Duah-Boateng I, Nyanful L, Francis O, Gyamerah EO, Godson A, Michael T, Kusan J, Fiawona B, Agyei-Dwarko D. 2026. Heat treatment responses in oil palm (Elaeis guineensis) genotypes and their impact on germination and seedling growth. Asian J Agric 10 (1): g100119. https://doi.org/10.13057/asianjagric/g100119. Seed dormancy in oil palm limits efficient propagation, necessitating optimized heat treatment to enhance germination and seedling growth. This study evaluated the effects of heat treatment duration and genotype using a 4×4 factorial randomized complete block design, involving four dura × pisifera hybrid progenies (61, 131, 132, and 136) and four heat durations (55, 60, 65, and 70 days). Key parameters measured included Germination Percentage (GP), Plant Height (PH), number of leaves, leaf length and breadth, butt circumference, Chlorophyll Content (CC, in SPAD units), and Stomatal Conductance (SC) were assessed under nursery conditions. Analysis of variance revealed significant progeny × duration interactions for GP, plant height, chlorophyll content, and stomatal conductance, indicating genotype-specific responses to heat treatment. Mean germination across treatments was high (90.52%), with the highest GP recorded in progeny 131 at 65 days (98.84%) and progeny 136 at 60 days (97.73%). Plant height varied significantly among treatments, reaching a maximum of 57.15 cm in progeny 131 at 60 days. In contrast, morphological traits such as leaf number, leaf size, and butt circumference showed no significant variation. Physiological traits were more responsive, with maximum chlorophyll content (54.31 SPAD units) and stomatal conductance (20.55 mmol m-² s-¹) observed in progeny 132 at 65 days. The results demonstrate that optimal heat treatment was identified as 60-65 days, with genotype-specific responses critical for maximizing germination and early seedling growth. The results could offer practical implications for certified seed production systems for maximizing germination efficiency and early seedling physiological performance in oil palm seed production systems.